Automated measurement of compression-decompression in arterial diameter and wall thickness by image-free ultrasound. (October 2020) - Raj, Kiran V; Joseph, Jayaraj; M, Nabeel P.; Sivaprakasam, Mohanasankar
Highlights: A fully automated method for the measurement intra-cardiac cycle changes in arterial diameter and wall thickness by image-free ultrasound. Method uses the Hilbert analytic phase information of A-mode radio-frequency data to delineate the various interfaces corresponding to the arterial wall layers. Method's performance was validated via simulations, controlled phantom experiments, and in-vivo trials. Reported technology being real-time, automated, and relatively inexpensive, is promising for large-scale field studies and low-resource settings. Abstract: Background and objective: The manual measurement of arterial diameter and wall thickness using imaging modalities demand expertise, and the state-of-art automated or semi-automated measurement features are seldom available in the entry-level systems. The advanced ultrasound modalities are expensive, non-scalable, and less favorable for field and resource-constrained settings. In this work, we present a novel method to measure arterial diameter (D), surrogate intima-media thickness (sIMT), and with them their intra-cardiac cycle changes by employing an affordable image-free ultrasound technology. Methods: The functionality of the method was systematically validated on a simulation testbed, phantoms and, 40 human subjects. The accuracy, agreement, inter-beat, and inter-operator variabilities were quantified. The in-vivo measurement performance of the method was compared against two reference B-mode tools – Carotid Studio and CAROLAB. Results: Simulations revealed that for the A-mode frames with SNR > 10 dB, the proposed method identifies the desired arterial wall interfaces with an RMSE < 20 μm. The RMSE for the diameter and wall thickness measurements from the static phantom were 111 μm and 14 μm, and for the dynamic phantom were 117 μm and 18 μm, respectively. Strong agreement was seen between the in-vivo measurements of the proposed method and the two reference tools. The mean absolute errors against the two references and the inter-beat variability were smaller than 0.18 mm for D and smaller than 36 μm for sIMT measurements. Likewise, the respective inter-observer variabilities were 0.16 ± 0.23 mm and 43 ± 25 μm. Conclusion: Acceptable accuracy and repeatability were observed during the validation, that were on a par with the recently reported B-mode techniques in the literature. The technology being real-time, automated, and relatively inexpensive, is promising for field and low-resource settings.